Proximal third humeral shaft fractures fixed with long helical PHILOS plates in elderly patients: benefit of pre-contouring plates on a 3D-printed model—a retrospective study - Qiuke Wang; Jian Hu; Junjie Guan; Yunfeng Chen; Lei Wang (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background To explore the clinical efficacy of 3D printing fracture models to assist in creating pre-contoured plates to treat proximal third humeral shaft fractures. Methods We retrospectively identified proximal third humeral shaft fractures treated between February 2012 and February 2015. The patients were divided into two groups according to the treatment procedure: a Synbone group and a 3D-printed group. In the Synbone group, long proximal humeral internal locking system plates were pre-contoured into helical shape on Synbones before surgery, while in the 3D-printed group, they were contoured on 3D-printed bone models. The pre-contoured plates were sterilized before surgery and were then used for fracture fixation during surgery. Duration of surgeries, blood loss volumes, the incidence of complications, and the time to fracture union were recorded, and functional outcomes were assessed by the Constant-Murley shoulder score and the Mayo Elbow Performance Score (MEPS) at 1-year follow-up. Results The subjects comprised 46 patients; 25 patients were allocated to the Synbone group and the remaining 21 to the 3D-printed group. There was no significant difference between the baseline characteristics of the two groups. At the 1-year follow-up visit, all fractures were healed and showed a satisfactory outcome. There were no instances of iatrogenic radial nerve injury, and there was no significant difference between the two groups with regard to fracture union time, Constant-Murley score, or MEPS score. Surgery duration was significantly shorter in the 3D-printed group compared to the Synbone group (42.62 vs. 60.36 min, P = 0.001), and the 3D-printed group lost less blood during surgery (105.19 vs. 120.80 ml, P = 0.001). In addition, in the 3D-printed group, 9 surgeries were finished by senior attending doctors and 12 were finished by junior attending doctors; however, there was no significant difference between the 1-year outcomes of the two grades of surgeons. Conclusions Our results show that the 3D printing technique is helpful in shortening the duration of surgery, reducing blood loss volume, and in making this surgical procedure easier for less-experienced surgeons. Trial registration This clinical study was registered in CHICTR on September 30, 2017 (number 17012852).